2016
DOI: 10.7860/jcdr/2016/16144.7952
|View full text |Cite
|
Sign up to set email alerts
|

Study of Aplastic Anaemia with Cyclosporine in Resource Poor Setting

Abstract: All patients presenting with symptoms of anaemia, petechiae, bruises and mucosal bleeds underwent a detailed clinical Keywords: Absolute neutrophil count, Antithymocyte globulin, Bone marrow transplantation Aim:The study was conducted with the aim to observe the treatment response in aplastic anaemia to Cycloserine-A. Materials and Methods:Patients who were diagnosed as AA and opted for Cyclosporine with informed consent were included in the study. All the subjects were started on 5mg/kg of Cyclosporine and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In group I, 50% of patients had no response at 12 months, 3 of them died later and one lost follow up. A lower response was reported in an Indian study done by Shetty et al [6], where out of 16 patients who completed the study, complete response (CR) was observed in 3 patients, partial response (PR) in 6 patients, a total of 9 out of 16 (56 %) responded.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In group I, 50% of patients had no response at 12 months, 3 of them died later and one lost follow up. A lower response was reported in an Indian study done by Shetty et al [6], where out of 16 patients who completed the study, complete response (CR) was observed in 3 patients, partial response (PR) in 6 patients, a total of 9 out of 16 (56 %) responded.…”
Section: Discussionmentioning
confidence: 70%
“…The positive response (CR + PR) to IST in this retrospective study was 70%, indicating IST as an effective therapy for AA patients. The hematopoietic response rate of AA patients for IST is reportedly 42-74%, with an overall long-term survival rate of approximately 90% across several large studies in the United States, Europe, and East Asia [5][6][7][8][9][10][11][12][13]. Our results were similar to a study done by Gu et al [14] that showed overall response of 77.66%, a study done by Tichelli et al [15] that was conducted on 192 patients, the overall response rate was 63±12%, and also similar to a study done by Groarke et al [16] where 28 (72%) of all treated patients achieved a response at 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we reported previously, tacrolimus showed durable response in majority of patients in both first-line and second-line treatment groups [24]. Although CsA had previously been the standard patients were switched to tacrolimus maintenance therapy due to poor response to Cyclosporin A (13,15,18,20) or intolerable toxicities (11,12,14,16,17,19,21). Of patients switched due to toxicities, patient #10 was in PR on CsA at the time of switching, and all other patients did not achieve desirable response on CsA; however, the primary reason to switch medication was development of toxicity which in most cases was AKI.…”
Section: Discussionmentioning
confidence: 78%
“…Differences in toxicity profiles between the two agents have been described in the solid organ transplantation literature and suggest that tacrolimus may be an attractive treatment alternative to cyclosporine. Toxicities associated with cyclosporine such as acute kidney injury, hypertension, neuropsychiatric symptoms, and cutaneous side effects such as gum hypertrophy and hirsutism are common, especially in women [ 18 , 19 ]. Tacrolimus causes less cutaneous toxicities in renal transplant patients, and is associated with less calcineurin inhibitor-associated nephrotoxicity [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%